Breadwinners and Losers: Does the Mental Health of Mothers, Fathers, and Children Vary by Household Employment Arrangements? Evidence From 7 Waves of Data From the Longitudinal Study of Australian Children. Issue 12 (14th July 2020) - King, Tania L; Shields, Marissa; Byars, Sean; Kavanagh, Anne M; Craig, Lyn; Milner, Allison
Abstract: In Australia, as in many industrialized countries, the past 50 years have been marked by increasing female labor-force participation. It is popularly speculated that this might impose a mental-health burden on women and their children. This analysis aimed to examine the associations between household labor-force participation (household employment configuration) and the mental health of parents and children. Seven waves of data from the Longitudinal Study of Australian Children were used, comprising 2004–2016, with children aged 4–17 years). Mental health outcome measures were the Strengths and Difficulties Questionnaire (children/adolescents) and 6-item Kessler Psychological Distress Scale (parents). A 5-category measure of household employment configuration was derived from parental reports: both parents full-time, male-breadwinner, female-breadwinner, shared-part-time employment (both part-time) and father full-time/mother part-time (1.5-earner). Fixed-effects regression models were used to compare within-person effects, controlling for time-varying confounders. For men, the male-breadwinner configuration was associated with poorer mental health compared with the 1.5-earner configuration (β  = 0.21, 95% confidence interval: 0.05, 0.36). No evidence of association was observed for either women or children. This counters prevailing social attitudes, suggesting that neither children nor women are adversely affected by household employment configuration, nor are they disadvantaged by the extent of this labor-force participation. Men's mental health appears to be poorer when they are the sole household breadwinner.